Channel estimation algorithms for OFDM systems. (16th November 2012) - Pradhan, Prasanta Kumar; Patra, Sarat Kumar; Faust, Oliver; Chua, Beng Koon
In this work we have applied Adapive Boosting (AdaBoost) for channel estimation of Orthogonal Frequency Division Multiplexing (OFDM) systems. The result of the AdaBoost algorithm was compared with other algorithms such Least Square (LS), Best Linear Unbiased Estimator (BLUE) and Minimum Mean Square Error (MMSE).